1992
DOI: 10.1083/jcb.117.6.1289
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar microtubule dynamics in Chlamydomonas: cytochalasin D induces periods of microtubule shortening and elongation; and colchicine induces disassembly of the distal, but not proximal, half of the flagellum

Abstract: Abstract. To study the mechanisms responsible for the regulation of flagellar length, we examined the effects of colchicine and Cytochalasin D (CD) on the growth and maintenance of Chlamydomonas flagella on motile wild type cells as well as on pf 18 cells, whose flagella lack the centrM microtubules and are immobile. CD had no effect on the regeneration of flagella after deflagellation but it induced fully assembled flagella to shorten at an average rate of 0.03 t~m-min I. Cells remained fully motile in CD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 29 publications
(49 reference statements)
2
52
1
Order By: Relevance
“…This mutation has essentially no effect on cell proliferation, although it does affect intraflagellar transport, flagellar regeneration, and fertilization-tubule formation (Kato et al 1993;Kato-Minoura et al 1997;Avasthi et al 2014). Moreover, although very high doses of cytochalasin D caused temporary shortening of the flagella (Dentler and Adams 1992), they had no effect on proliferation (Harper et al 1992).…”
mentioning
confidence: 99%
“…This mutation has essentially no effect on cell proliferation, although it does affect intraflagellar transport, flagellar regeneration, and fertilization-tubule formation (Kato et al 1993;Kato-Minoura et al 1997;Avasthi et al 2014). Moreover, although very high doses of cytochalasin D caused temporary shortening of the flagella (Dentler and Adams 1992), they had no effect on proliferation (Harper et al 1992).…”
mentioning
confidence: 99%
“…Although colchicine blocked flagellar growth and did not stimulate shortening, it did not affect the exchange of other axonemal or membrane plus matrix components. Colchicine induces flagellar shortening in pf18 cells treated with low levels of red light and in pf18 and wild-type cells treated with cytochalasin D (14), but these appear to reflect unique properties of pf18 (13,14) and a yet unexplained effect of cytochalasin D on flagellar length. Axonemal protein exchange may make the axonemes more responsive to signals that regulate length, but turnover alone does not appear to drive flagellar length changes.…”
mentioning
confidence: 99%
“…2 and Rosenbaum (36) reported the incorporation of epitopetagged tubulin in nongrowing flagella, but the exchange of other flagellar components was not examined. Recent discoveries of the importance of the IFT motors kinesin-II and cytoplasmic dynein in flagellar assembly and maintenance in a variety of organisms (16,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) combined with earlier studies showing that flagellar growth and/or shortening can be induced by light (13), various drugs and ions (12)(13)(14), and temperature (15,24), prompted a careful examination of protein turnover in steady state Chlamydomonas flagella. Our experiments confirm that more than 80 different polypeptides are exchanged with a cytoplasmic protein pool in steady state flagella.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The abundant presence of Bug22 in the axoneme and its tight association with axonemal microtubules might provide stability and stiffness to the axoneme. It has been shown that the proximal half to two-thirds of the flagellum is more stable and resistant to drug-induced flagellar shortening (Dentler and Adams, 1992). It has also been proposed that Bug22 in Paramecium might regulate cilia rigidity (Laligné et al, 2010).…”
Section: Bug22 Associates With All Axonemal Microtubulesmentioning
confidence: 99%